Получение в условиях высоких давлений и температур наноструктурных композитов и нструментального назначения - Шульженко, А.А.; Соколов, А.Н.; Олейник, Г.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The present paper reports the results of sintering statically synthesized nanopowders in the presence of sintering aids. The observed peculiarities of the sample grain structure allow a conclusion that the in sintering of diamonds, the recrystallization with participation of the liquid phase takes place. A combination of the mechanical preactivation of the initial reaction mixture by adding the sintering aids allows one to essentially increase physico-mechanical characteristics of the high pressure-high temperature sintered diamond nanocomposite. This is achieved first of all because of the homogeneity of the microstructure of the sintered composite and because of the microcracking is suppressed by sintering aids.